Identification of the Components Involved in Cyclic Di-AMP Signaling in Mycoplasma pneumoniae - Blötz, Cedric; Treffon, Katrin; Kaever, Volkhard; Schwede, Frank; Hammer, Elke; Stülke, Jörg (Frontiers in Microbiology, 2017)
Bacteria often use cyclic dinucleotides as second messengers for signal transduction. While the classical molecule c-di-GMP is involved in lifestyle selection, the functions of the more recently discovered signaling nucleotide cyclic di-AMP are less defined. For many Gram-positive bacteria, c-di-AMP is essential for growth suggesting its involvement in a key cellular function. We have analyzed c-di-AMP signaling in the genome-reduced pathogenic bacterium Mycoplasma pneumoniae. Our results demonstrate that these bacteria produce c-di-AMP, and we could identify the diadenylate cyclase CdaM (MPN244). This enzyme is the founding member of a novel family of diadenylate cyclases. Of two potential c-di-AMP degrading phosphodiesterases, only PdeM (MPN549) is active in c-di-AMP degradation, whereas NrnA (MPN140) was reported to degrade short oligoribonucleotides. As observed in other bacteria, both the c-di-AMP synthesizing and the degrading enzymes are essential for M. pneumoniae suggesting control of a major homeostatic process. To obtain more insights into the nature of this process, we have identified a c-di-AMP-binding protein from M. pneumoniae, KtrC. KtrC is the cytoplasmic regulatory subunit of the low affinity potassium transporter KtrCD. It is established that binding of c-di-AMP inhibits the KtrCD activity resulting in a limitation of potassium uptake. Our results suggest that the control of potassium homeostasis is the essential function of c-di-AMP in M. pneumoniae.